Salatiga as Vacantie Oord: Representations of Colonial Rest Towns in Central Java, Late 19th to Early 20th Century: Salatiga Sebagai Vacantie Oord: Representasi Kota Peristirahatan Kolonial di Jawa Tengah Akhir Abad ke-19 sampai Awal Abad ke-20 - Nuha, Ulin; Ibnu Sodiq (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines how the city of Salatiga was constructed and represented as a vacantie oord or colonial resort town by the Dutch East Indies government in the late 19th to early 20th centuries. Using a historical qualitative approach, this paper seeks to reconstruct Salatiga's strategic role within the network of colonial cities in Central Java by examining aspects of urban planning, administrative regulations, and the colonial narratives that emerged during that period. Primary sources used include official colonial documents such as Staatsblad van Nederlandsch-Indië No. 266 of 1917, city map archives, colonial photographs, and tourist brochures published by the Toeristenverkeer institution. This research also utilizes secondary literature on colonial urban history and tropical spatial studies. The results of the study show that Salatiga was chosen as a resort town because of its strategic location on the slopes of Mount Merbabu, its cool climate, clean air, and the presence of natural water sources. The colonial government actively developed the urban layout of Salatiga through the construction of villas, hotels, parks, and recreational facilities that supported the city's image as a place of recovery and relaxation for the European elite. This study demonstrates that the image of a vacantie oord not only reflected colonial recreational needs but also served as an instrument of power manifested through the physical forms of the city.